2022
DOI: 10.1515/arh-2022-0128
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of four different cogeneration cycles by using some criteria

Abstract: The purpose of this article is to evaluate four different gas turbine cogeneration cycles which are basic, absorption cooling, air heating and air fuel heating cogeneration cycles by using the most important six evaluation criteria for different excess air coefficient, different compression rates, and different compressor inlet air temperatures. These six evaluation criteria are electrical heat ratio, exergy efficiency, incremental heat rate, artificial thermal efficiency, fuel energy saving ratio, and specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…Buradan elde edilen yüksek sıcaklık ve basınçlı toluen buharı, bir buhar türbininden genişletilerek güç elde edilir ve bu güçten bir elektrik jeneratörü ile elektrik üretilir. Buhar türbini çıkışındaki düşük basınç ve sıcaklığa sahip toluen buharı, kondensere verilir ve burada yoğuşma ısısı atılarak daha soğutulur ve yoğuşturulur [7,8]. Kondenserden yoğuşarak çıkan sıvı toluen pompaya verilerek yüksek basınca çıkarılır ve ısı değiştiricisine toluen buharı elde edilmek üzere verilir.…”
Section: Materyal Ve Yöntemunclassified
“…Buradan elde edilen yüksek sıcaklık ve basınçlı toluen buharı, bir buhar türbininden genişletilerek güç elde edilir ve bu güçten bir elektrik jeneratörü ile elektrik üretilir. Buhar türbini çıkışındaki düşük basınç ve sıcaklığa sahip toluen buharı, kondensere verilir ve burada yoğuşma ısısı atılarak daha soğutulur ve yoğuşturulur [7,8]. Kondenserden yoğuşarak çıkan sıvı toluen pompaya verilerek yüksek basınca çıkarılır ve ısı değiştiricisine toluen buharı elde edilmek üzere verilir.…”
Section: Materyal Ve Yöntemunclassified
“…Needless equipment decreases the performance and advantages of the cycle. Also, Karaali and Keven, (2022) investigated four different cogeneration cycles' efficiencies, the effect of absorption cooling of inlet air of compressor and the effect of adding recuperators into these cycles, on the working conditions [12,13,14]. They found that absorption cooling by using waste heat can help to improve the efficiencies and the working conditions of the four cogeneration systems.…”
Section: Introductionmentioning
confidence: 99%
“…In their parametric studies, they showed the best working conditions of this plants and systems. * Corresponding author: rabikar@gmail.com Karaali and Keven [3,4], in their researches they have calculated parametric performance analyses of the three various cogeneration systems those were named basic, air heating, absorption cooling, and air-fuel heating cogeneration systems.…”
Section: Introductionmentioning
confidence: 99%